2017
DOI: 10.17979/sportis.2017.3.3.2051
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación de la actitud del profesorado de educación física ante alumnos con Necesidades Educativas Especiales

Abstract: ResumenEl presente estudio analiza cómo es la actitud de los profesores de Educación Física ante Alumnos con Necesidades Educativas Especiales, en relación a la titulación, edad y sexo. La metodología es cuantitativa y transversal, con una muestra de 40 profesores de la Comunidad de Madrid de Primaria y Secundaria. Para el análisis de los resultados se ha optado por un análisis bivariable a través de tablas de contingencia, dando como resultado una relación moderada entra la variable actitud con la edad (Ø= .4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Of the eighteen studies that analyzed the influence of gender, seven found that women tend to be more positive [20][21][22][23][24][25][26] and four found that men have better attitudes [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the eighteen studies that analyzed the influence of gender, seven found that women tend to be more positive [20][21][22][23][24][25][26] and four found that men have better attitudes [27][28][29][30].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, in ten studies the attitudes are mixed: five of them are in-service teachers' studies [26,33,35,44,50], three are pre-service teachers' research [24,37,57], another one is a mixed study with in-service and preservice teachers [61], and the last one that found mixed attitudes was conducted just with special education teachers [32]. In three other cases, teachers' attitudes toward inclusion tended to be even negative [22,30,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation